An Overview on Potential Problems and Solution of Hybrid Microgrids - Kandasamy, Jeevitha; Ramachandran, Rajeswari (Journal of Electronics and Informatics, 2023)
The world's energy demand has increased significantly in the past two decades, and there is a growing concern over energy security and adequacy. The use of renewable energy sources and microgrids can play a significant role in ensuring a sustainable energy future. Effective energy resource planning is critical to achieving global commitments towards sustainable development. It involves managing and optimizing the supply and storage of energy resources, including renewable energy sources. Microgrids can contribute to this effort by improving the efficiency of energy systems and reducing energy losses. Hybrid microgrids, which combine multiple energy resources and storage systems, offer several benefits for energy management and optimization. However, integrating renewable energy sources into the existing energy system can pose several challenges, such as voltage and frequency regulation, low-inertia issues, and system stability. Researchers have been working on developing advanced control strategies and optimization techniques, including metaheuristic optimization techniques, to address these challenges and improve the performance of hybrid microgrids. Overall, energy resource management and the use of microgrids and renewable energy sources are essential for achieving a sustainable energy future and mitigating the impacts of climate change.
Keywords: Hybrid microgrid; Frequency control; Energy management system